2018
DOI: 10.18203/2319-2003.ijbcp20184697
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin plus fenofibrate in diabetic dyslipidemia: a hospital record based study

Abstract: Background: Cardiovascular diseases (CVD) are the leading cause of death throughout world population each and every year. Focus on dyslipidemia management is urgently required in India to halt the rising tide of CVD. The purpose of diabetic dyslipidemia study is a record based one, to find out the effect of Rosuvastatin plus Fenofibrate, in adult Type 2 diabetes with dyslipidemia, with high TGL/HDL ratio in Lipid profiles, in a tertiary care hospital in the Union territory of Puducherry.Methods: There were 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…8 In present study, dyslipidemia is associated with CAD which was statically significant similar to previous study done by Saha et al, and a good control of dyslipidemia will prevent CAD. 9,10 Hypertension was found to be an important risk factor for CAD in present study similar to previous study done by Aykan et al 11 In present study single vessel disease was more common than double and triple vessel disease as noted by Jegavanthan et al, in their study. 12 In another study, it was reported that acute coronary syndrome (ACS) occurs more among males than females in younger age groups.…”
Section: Discussionsupporting
confidence: 89%
“…8 In present study, dyslipidemia is associated with CAD which was statically significant similar to previous study done by Saha et al, and a good control of dyslipidemia will prevent CAD. 9,10 Hypertension was found to be an important risk factor for CAD in present study similar to previous study done by Aykan et al 11 In present study single vessel disease was more common than double and triple vessel disease as noted by Jegavanthan et al, in their study. 12 In another study, it was reported that acute coronary syndrome (ACS) occurs more among males than females in younger age groups.…”
Section: Discussionsupporting
confidence: 89%